Twelver Shi’ite Islam: Conceptual and Practical Aspects - Christoph, Marcinkowski (2016)
Recent political events surrounding the Iranian “nuclear crisis”, as well as the still unsettled fate of Iraq have resulted in a renewed interest in the Shi’ite dimension of Islam among political observers. This paper attempts to present an outline of some of the “essential features” of Twelver Shi’ite Islam as it distinguishes itself today from majority Sunnism. In particular, the different approaches of Sunnite and Shi’ite Muslims towards the issue of religious and political authority - resulting in history often in violent clashes - have been highlighted. Moreover, throughout their history, Shi’ites had put high emphasis on intellectual pursuit and reasoning, on philosophy and science. Although the paper focuses of the “Twelver Shi’ites” (today numerically and politically the strongest Shi’ite group), the today rather un-political Ismā‘īlīs or “Sevener” Shi’ites, too, shall be referred to briefly, as they have also some pockets in Singapore among the Indian Muslim community. Of special interest to the political observer of contemporary Islam shall be the status of Shi’ite clerics (Arab. ‘ulamā’) vis-à-vis their Sunnite colleagues.